Regional citrate and systemic heparin are adequate to maintain filter half‐life for COVID‐19 patients on continuous renal replacement therapy. Issue 4 (9th February 2022) - Chiao, Cassandra; Faust, Hilary; Singh, Tripti
Abstract: Introduction: The aim of our study is to compare clotting of CRRT filters in patients with COVID‐19‐associated AKI versus septic shock‐associated AKI. Methods: Retrospective study of adult ICU patients with COVID‐19 compared to those with septic shock admitted to a tertiary hospital April–October 2020. Independent t test and chi‐square test used to determine statistical significance of CRRT filter clotting between the two groups. Time‐to‐event data analyzed with Kaplan–Meier curves. Analyses performed on Microsoft Excel and MedCalc. Results: Twenty‐seven ICU patients with AKI requiring CRRT were included, 13 with COVID‐19 and 14 non‐COVID‐19 patients with septic shock. The mean half‐life of CRRT hemofilter was similar in COVID‐19 patients compared to non‐COVID‐19 patients (27.4 vs. 27.5 h, p  = 0.79). The number of CRRT hemofilter changes per day was similar in both groups (0.6 filter changes per day, p  = 0.84). However, significantly more patients with COVID‐19 were on systemic heparin (69% vs. 13%, p  = 0.02). Conclusion: We found that COVID‐19 patients with AKI requiring CRRT had similar CRRT hemofilter half‐life compared with sepsis‐associated AKI patients with use of regional citrate and systemic heparin. Further studies are needed to find which methods of anticoagulation are optimal in patients with COVID‐19 infection with AKI requiring CRRT.